Contents basal levels of sex hormones and pituitary hormones in patients demodecosis - Bodnya, K; Revenko, Zh (Annals of Mechnikov’s Institute, 2020)
The regularities of changes in the nature and dynamics of clinical – hormonal parameters are revealed in this research that are not being specific they expand knowledge of the pathogenesis of demodicosis and create certain conditions for the directed correction of compensatory and adaptive capabilities of the host and open up prospect for improvement – pathogenetic treatment of demodicosis and its complications.